KEKUATAN AKTA NOTARIS DALAM MENJAMIN HAK KEPERDATAAN - Rahmawati Boty (JCH (Jurnal Cendekia Hukum), 2017)
Notarial Deed is be able guarantee the civil rights of the legal subject, after authentic agreement and determination, so that there is no approval of the cancellation of the parties, the right of civilization of the legal subject can not be contested. The type of research conducted is a Normative Juridical legal research which is about what becomes the Strength of Notarial Deed in guaranted the Right of civilization. This research have The role and function of the Notary deed to the legal relationship between legal subjects is to formalizd the contents. The legal power of notarial deed if used as a means of verification in civil cases is as perfect or formal evidence. Losses in the responsibility of a notary when doing negligence to the client. Notary's role in making deed either in legal theory or practice is Notary also assigned to do registration and validated the letters / deeds made under the hand.